Radiological anatomy of the lumbar pedicles in malay population using reformatted computed tomography images - Mughir, Abdullah Mohamed Abdo (2008)
Overview: The nonnal measurements of the lumbar pedicles well provide crucial information for spinal instrumentation, spinal management and useful guidelines for the use of devices. One of the spinal instrumentation used through the pedicle is pedicle screw as a fixation device for poste1ior spinal instmmentation. The use of pedicle screw had become increasingly popular in the recent years. For proper implant placement. an accurate knowledge of the pedicle morphology is of utmost importance for the safe placement of pedicle screw. Improper implant placement will lead to devastating neurological consequences to the patient. Objectives: The main objective of this study was to obtain a database for the morphometry of lumbar pedicles from LI to L5 of the normal Malay population treated in Hospital USM. Methodology: hundred twenty six (126) patients (74 adults and 52 pediatrics) were included in this cross-sectional retrospective study. Archived Computed Tomography (CT) images of abdomen performed for those patients diagnosed of cancer for the purpose of staging or for other abdominal pathologies were obtained from the Radiology Department of Hospital Universiti Sains Malaysia. Axial CT scan images of lumbar vertebrae (LI to LS) were obtained using a General Elect1ic CT scanner (GE Medical Overview: The nonnal measurements of the lumbar pedicles well provide crucial information for spinal instrumentation, spinal management and useful guidelines for the use of devices. One of the spinal instrumentation used through the pedicle is pedicle screw as a fixation device for poste1ior spinal instmmentation. The use of pedicle screw had become increasingly popular in the recent years. For proper implant placement. an accurate knowledge of the pedicle morphology is of utmost importance for the safe placement of pedicle screw. Improper implant placement will lead to devastating neurological consequences to the patient. Objectives: The main objective of this study was to obtain a database for the morphometry of lumbar pedicles from LI to L5 of the normal Malay population treated in Hospital USM. Methodology: hundred twenty six (126) patients (74 adults and 52 pediatrics) were included in this cross-sectional retrospective study. Archived Computed Tomography (CT) images of abdomen performed for those patients diagnosed of cancer for the purpose of staging or for other abdominal pathologies were obtained from the Radiology Department of Hospital Universiti Sains Malaysia. Axial CT scan images of lumbar vertebrae (LI to LS) were obtained using a General Elect1ic CT scanner (GE Medical outer and inner diameter, lateral cortical thickness at L2, transverse pedicle angle at L3- L5, however there were no significant statistical differences between male and female in medial coitical thickness. lateral cortical thickness except L2,pedicle length, transverse pedicle angle except L3 and sagittal angle except L3-L5. A significant statistical difference in transverse outer, inner diameter and pedicle length between pediatrics and adult in male all at levels ,medial cortical thickness, lateral cortical thickness ,transverse pedicle angle and sagittal angle at almost all levels in male. No significant statistical difference between pediatrics and adult in female group at almost all levels in transverse outer and inner diameter, medial and lateral co1tical thickness, pedicle length, sagittal angle. Conclusion: The trends of our measurements were same as the western and other Asian population. However our measurements were close to other Asian and smaller compare to westerns. Almost there were no significant differences between right and left in pediatric group and also the adult group except the transverse outer diameter in adult group. There were significant differences between male and female in almost all levels, however these differences were noted in outer and ilmer diameter in pediatric group.